CULTURAL-BASED READING MATERIALS FOR VOCATIONAL HIGH SCHOOL: STUDENTS’ NEED ANALYSIS - Jopalina, Praisa; Inderawati, Rita; Petrus, Ismail (University of Kuningan, 2023)
English instruction provided in vocational schools (SMK) possesses distinct characteristics when compared to English instruction in general schools. Considering the vocational schools' objective of preparing students to compete effectively in the workforce, it becomes necessary to adapt the instructional materials to cater to the students' specific needs. This research aims to identify the requirements of students in developing culturally-based English reading materials, as assessed from the perspectives of both students and teachers. A combination of questionnaires and interviews was employed to gather the necessary information. A comprehensive analysis, encompassing both quantitative and qualitative aspects, was conducted on the collected data. The findings of the needs assessment unveiled the following key points: 1) students continue to face difficulties in understanding what they read; 2) there is a demand for descriptive texts; 3) English reading materials should be integrated with content relevant to other subjects; and 4) no English reading materials currently exist that consider the students' local culture, specifically the Prabumulih culture. To fulfill these requirements, it is imperative to create supplementary reading resources that incorporate local culture, align with the students' reading proficiency, and support the subject matter effectively.